International Development Lending and Global Value Chains in Africa - Vito Amendolagine (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
As the world becomes more and more integrated, participating in global production fragmentation by connecting to global value chains (GVCs) can provide a "golden" opportunity for developing countries to access international markets and boost economies. Vito Amendolagine analyses the extent to which international development lending can support African countries in trading intermediate goods with foreign partners with the goal of further specializing in high value-added activities within cross-national production networks. Based on his research, it appears that Chinese lending increases the involvement of borrowing countries in the international trade of intermediate goods, while World Bank loans contribute to move African countries toward higher valued added activities along international production chains.
Keywords: 330